Pharmacology Studies: Hints for a Change in the Paradigm - The Editorial Board, The Editorial Board (Organisms. Journal of Biological Sciences, 2020)
Citation: The Editorial Board, 2020, “Pharmacology Studies: Hints for a Change in the Paradigm”, Organisms: Journal of Biological Sciences, vol. 4, no. 1, pp. 157-159. DOI: 10.13133/2532-5876/16973.